2011
DOI: 10.1007/s00441-011-1275-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β in chronic kidney disease: an integration of tubular, glomerular and vascular effects

Abstract: Transforming growth factor beta (TGF-β) has been recognized as an important mediator in the genesis of chronic kidney diseases (CKD), which are characterized by the accumulation of extracellular matrix (ECM) components in the glomeruli (glomerular fibrosis, glomerulosclerosis) and the tubular interstitium (tubulointerstitial fibrosis). Glomerulosclerosis is a major cause of glomerular filtration rate reduction in CKD and all three major glomerular cell types (podocytes or visceral epithelial cells, mesangial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(209 citation statements)
references
References 120 publications
(124 reference statements)
2
195
0
12
Order By: Relevance
“…In MMCs, it has been proved that TGF-β1/Smad3 signaling pathway could stimulates the synthesis and accumulation of ECM, and is associated with MMC hypertrophy in diabetes [12]. Here, we demonstrated that TGF-β1 and Smad3 mediated high glucose-induced Matrilin-2 activation in MMCs.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In MMCs, it has been proved that TGF-β1/Smad3 signaling pathway could stimulates the synthesis and accumulation of ECM, and is associated with MMC hypertrophy in diabetes [12]. Here, we demonstrated that TGF-β1 and Smad3 mediated high glucose-induced Matrilin-2 activation in MMCs.…”
Section: Discussionmentioning
confidence: 53%
“…In renal diseases, TGF-β1 is upregulated and stimulates MMCs to produce ECM proteins, including type I, III and IV collagen, and laminin, contributing to glomerular ECM accumulation [12,26]. In MMCs, it has been proved that TGF-β1/Smad3 signaling pathway could stimulates the synthesis and accumulation of ECM, and is associated with MMC hypertrophy in diabetes [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infancy/childhood, the most overt cause of CKD and end-stage renal disease is birth defects or congenital anomalies of the kidney and urinary tract that result in inadequate renal mass to provide internal physiologic homeostasis for the provision of growth and development (NAPRTCS 2011;Chen et al 2012;Bagby 2015;Puddu et al 2009;Chiang et al 2010;Hsu et al 2014;Greenbaum et al 2011;Horbar et al 2012;Hack et al 2002;Stelloh et al 2012;Gilbert et al 1990;Lelievre-Pegorier et al 1998;Sutherland et al 2012a;Ortiz et al 2001;Brenner and Anderson 1987;Reidy and Kaskel 2007;Fogo 2007;Lopez-Hernandez and Lopez-Novoa 2012;Gubhaju et al 2009;Sutherland et al 2012b;White et al 2009;Bacchetta et al 2009;KeijzerVeen et al 2010;Rademacher and Sinaiko 2009;Salgado et al 2009; Centers for Disease Control and Prevention (CDC) 2007; Hodgin et al 2009a;Harambat et al 2012;Warady and Chadha 2007;Tabel et al 2010;Sanna-Cherchi et al 2009). The long-term consequences of prematurity on renal mass are more subtle but, as mentioned above, are becoming increasingly clear.…”
Section: Prematurity: An Underrecognized Risk Factor For Ckdmentioning
confidence: 99%
“…Abnormalities in these pathways lead to the spectrum of congenital anomalies of the kidney and urinary tract (Reidy and Rosenblum 2009). While the majority of over 70 genes identified are associated with syndromes involving multiple congenital anomalies, human genetic studies have confirmed a role for defects in several genes in non-syndromic congenital anomalies of the kidney and urinary tract, including HNF1, PAX2, ROBO2, GDNF, RET, SPRY1, FREM, FRET, and the angiotensin receptor 2 gene (Horbar et al 2012;Hack et al 2002;Stelloh et al 2012;Gilbert et al 1990;Lelievre-Pegorier et al 1998;Sutherland et al 2012a;Ortiz et al 2001;Brenner and Anderson 1987;Reidy and Kaskel 2007;Fogo 2007;Lopez-Hernandez and Lopez-Novoa 2012;Gubhaju et al 2009;Sutherland et al 2012b;White et al 2009;Bacchetta et al 2009;KeijzerVeen et al 2010;Rademacher and Sinaiko 2009;Salgado et al 2009; Centers for Disease Control and Prevention (CDC) 2007; Hodgin et al 2009a;Harambat et al 2012;Warady and Chadha 2007;Tabel et al 2010;Sanna-Cherchi et al 2009;Westland et al 2011;Spencer et al 2011;BertoliAvella et al 2008;Nishimura et al 1999;Song and Yosypiv 2011;Paces-Fessy et al 2012;Chatterjee et al 2012;Nakayama et al 2010;Saisawat et al 2012;Weber et al 2006). In addition to genetic mutations, prenatal environmental influences such as exposures to renin-angiotensin inhibition or antiepileptic...…”
Section: Renal Development and Genetic Abnormalitiesmentioning
confidence: 99%